Problem of Definition of Personal Security in the Modern Russian Criminal Procedure - ZAYTSEV, Oleg; GRINENKO, Aleksander; MAKEEVA, Inna; ZEINALOVA, Larisa; TASAKOV, Sergei; SLED, Yurii; EPIKHIN, Alexander; MISHIN, Andrei (Journal of Advanced Research in Law and Economics, 2017)
The article represents comparison of various definitions and concepts related to the phenomenon of providing a secured protection of individuals participating in the Russian criminal procedure.
Keywords: individual; public protection; security; security of person; criminal procedure; criminal case; proceeding on a case; crime prevention; protection of witnesses; protection of victims